Answer:
8x +3
Step-by-step explanation:
Just collect the like terms, like terms have the same variable. So in this case, 2x, 3x, 3x all share the variable x, so we can add it together.
So when simplified:
2x +3x + 3x+ 3 = 8x +3
Hope this helped,
Cate
A. y=0.5x
B y=-2x
C y=6x
D y=12
16x-7≤-71
Add 7 to both sides
16x≤-64
Divide both sides by 16
x≤ -4
Hope this helps! :)
I believe the answer is
26
sorry if wrong
if not an answer choice then 168.
The factor outside the parentheses is -1. Distribute using that factor.
2 - (4 - <em>x</em>) = 7<em>x</em> - 5<em>x</em>
<em />
-1 * 4 = -4 and -1 * -<em>x</em> = <em>x</em>
<em />
2 - 4 + <em>x</em> = 7<em>x</em> - 5<em>x</em>
Simplify.
-2 + <em>x</em> = 2<em>x</em>
<em>x</em> = 2<em>x</em> + 2
-<em>x</em> = 2
<em>x</em> = -2
<h3>
Answer:</h3>
<em>x</em> = -2